2019
DOI: 10.1111/dar.12977
|View full text |Cite
|
Sign up to set email alerts
|

The availability and acquisition of modafinil on the internet

Abstract: Introduction and Aims Prescription medications are readily accessible on both the dark and surface web. This study focuses specifically on modafinil. Modafinal is a medication that is used to treat sleepiness due to a range of sleep disorders, but is also used off‐label as a cognitive enhancer. This study aimed to evaluate surface websites which sold modafinil to Australia to provide an overview of and to document the characteristics of surface web retailers. Design and Methods An online search to identify onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Yet, the fact that significant proportions of the users of these CEs reported negative side effects points to the downside of these drugs and provides support for a balanced and evidence-based discussion of costs and benefits as part of education campaigns and clinical interventions in university health services. While most users accessed their CEs from friends, over half the users of modafinil accessed it online, a finding consistent with recent work showing that modafinil is readily accessible in Australia through overseas sites via the surface web [38]. The risks of importing prescription medications into Australia without a valid prescription, along with the issues of counterfeit medications sold online, are also relevant for student education and health service interventions.…”
Section: Discussionsupporting
confidence: 73%
“…Yet, the fact that significant proportions of the users of these CEs reported negative side effects points to the downside of these drugs and provides support for a balanced and evidence-based discussion of costs and benefits as part of education campaigns and clinical interventions in university health services. While most users accessed their CEs from friends, over half the users of modafinil accessed it online, a finding consistent with recent work showing that modafinil is readily accessible in Australia through overseas sites via the surface web [38]. The risks of importing prescription medications into Australia without a valid prescription, along with the issues of counterfeit medications sold online, are also relevant for student education and health service interventions.…”
Section: Discussionsupporting
confidence: 73%
“…A majority of these websites listed possible desired effects such as increased alertness, improved memory, increased concentration and productivity and performance enhancement. Similarly, Dursun et al (2019) found that 13 websites sold modafinil to consumers in Australia without prescription, with a median price of 118 Australian dollars (81 USD) for 90,150 mg pills. Such availability of unprescribed modafinil only fuels the already existing ethical controversy.…”
Section: Clinical Indications and Side Effectsmentioning
confidence: 99%
“…A primary consequence of illicit drug markets and the absence of regulation is the variable quality or purity of the final product [1], and for those substances which are illegal or used non-medically, there is a risk that substances may be of unknown quality or contain unknown impurities [2]. Counterfeit drugs have become a global problem and have increased with the expansion of the Internet [3][4][5]. Counterfeit drugs are considered by the Australian Therapeutic Goods Administration (TGA) and the World Health Organization (WHO) as those which are substandard and falsified, and either fail to meet quality standards or are deliberately manufactured to imitate a legitimate product [6,7].…”
Section: Introductionmentioning
confidence: 99%